An Incentive Approach to Identifying Financial System Vulnerabilities - Chai, Jingqing (IMF Working Papers; Working Paper, 2000)
This paper underscores the importance of the assessment of incentives of the main agents in a financial system as a key element in the analysis of financial system vulnerability and the surveillance over the financial system. We outline a diagnostic approach for the assessment of incentives. This approach highlights the need for additional research on the relationship between institutional structures and financial vulnerabilities.